12. Interactive Groups: Examining and Interrogating Issues of Heterogeneity and Accountability - Gail Frost (Collected Essays on Learning and Teaching, 2011)
Teachers and learners alike bring past experiences into present teaching and learning contexts. Group work is an experience that carries equal measures of joyful anticipation and mournful trepidation. Learners typically experience group work as an uneven distribution of time, competence, and accountability, and seem to have lingering memories of one or two people doing all the work in order to salvage a respectable grade. While students must understand the group process when they work in problem- or inquiry-based teams, we think the onus should also be on the instructor to devise methods of equity and accountability, which address the aforementioned justifiable fears. Our paper will describe several strategies we have used to anticipate and offset the inevitable tensions and contingencies inherent in group work.